Contraception: Stopping sperm in their tracks - McGoldrick, Luke L; Chung, Jean-Ju (eLife, 2020)
An automated high-throughput platform can screen for molecules that change the motility of sperm cells and their ability to fertilize.
Keywords: sperm; contraception; motility; infertility; acrosome reaction; high-throughput screening